Research in organizational change and development. Vol. 28 - Noumair, Debra A.; Shani, Abraham B. (Emerald Publishing Limited, 2020)
Volume 28 of Research in Organizational Change and Development introduces thought-provoking contributions. These include: Utilizing big data and social network analysis in OD; professional identity of renowned American women in the field; the role of communities that support interpersonal learning and enhance workers ability to thrive in the emerging nature of the new world of work; technology and technological embeddedness as a change and development enabler in schools; organizational resilience as an arena for organization development work; change in tightly coupled systems and the middle management role in organization development; and strategic fitness processes and organizational dialogue. The diverse collaborative contributions by leading scholars and scholar-practitioners provide an enriching body of knowledge on contemporary challenges in organizational change and development.